We can rewrite radicals as fractional exponents, like the following example
![\sqrt[y]{x}=x^{(1)/(y)}](https://img.qammunity.org/2023/formulas/mathematics/college/cx29ds43e3lir85jn67pd2y93s3394if2w.png)
Using this rule in our problem, we can rewrite our expression as
![\sqrt[4]{5}\sqrt[16]{5}=5^{(1)/(4)}\cdot5^{(1)/(16)}](https://img.qammunity.org/2023/formulas/mathematics/college/190nvucji61r2w0vq5ttq405euexq0ttcp.png)
When we have a product of two exponentials with the same basis, we just add the exponents.
![a^b\cdot a^c=a^(b+c)](https://img.qammunity.org/2023/formulas/mathematics/college/82fvnnifbni1r5kvi35zhdrr76aio7iw11.png)
Using this property in our problem, we have
![5^{(1)/(4)}\cdot5^{(1)/(16)}=5^{(1)/(4)+(1)/(16)}=5^{(4)/(16)+(1)/(16)}=5^{(5)/(16)}=\sqrt[16]{5^5}=\sqrt[16]{3125}](https://img.qammunity.org/2023/formulas/mathematics/college/x8ig2vpwmast268iwj7tdozs4urrgpfdhm.png)
And this is our result.
![\sqrt[4]{5}\sqrt[16]{5}=\sqrt[16]{3125}](https://img.qammunity.org/2023/formulas/mathematics/college/ily61euvaprk48y8zijya7rxcmxltfecq0.png)